A study on factors that contribute to inflation : A case study of Malaysia, Indonesia and Thailand / Nur Marini Mohamed Nor - Mohamed Nor, Nur Marini (Faculty of Business and Management, 2007)
This project paper attempts to identify important factors that contribute significantly to inflation in Malaysia, Indonesia and Thailand. This study also is aimed to examine the possible existence of international and intra-ASEAN inflation transmission to Malaysia, Indonesia and Thailand and to know which variable is the most that influence inflation in each country .This study covered thirteen years period from 1993 to 2005 for research in Malaysia, twelve years period from 1994 to 2005 for research in Thailand and five years period from 2001 to 2005 for research in Indonesia. This study applied multiple linear regression programs in order to analyse the relationship between dependent variable and independent variables. From the analysis, the findings show that ASEAN inflation have significant relationship with Malaysia inflation rate. The largest effect on Malaysia Inflation rate is Thailand Inflation rate. For Indonesia, the relationship between Indonesia interest rate, Thailand inflation and both of the foreign exchange rate with the Indonesia inflation rate have significant level and the largest effect on Indonesia Inflation rate is the foreign exchange rate (Japanese Yen) while for Thailand, Thailand interest rate, Hong Kong Dollar and Malaysia Inflation rate have significant relationship with Thailand inflation rate and the largest effect on the country's inflation rate is Thailand interest rate.